Evaluation of a re-useable bronchoscopy biosimulator with ventilated lungs - Garner,JL; Garner,SD; Hardie,RJ; Molyneaux,PL; Singh,S; Kemp,SV; Shah,PL (ERJ Open Research, 2019)
Background: Restrictions on respiratory trainee time and access to procedures reduce the opportunities toacquire necessary skills in bronchoscopy. Simulation, not subject to such impediments, is a usefulsupplementary aid to teaching bronchoscopic techniques in a safe environment but there is a limitedchoice of simulators that are sufficiently realistic and not prohibitively expensive. This study evaluated alow-cost device that simulates an intubated and ventilated patient, employing re-useable, inflatable,BioFlex-preserved, porcine lungs.Methods: 26 bronchoscopists, trainee and experienced, after using the bronchoscopy biosimulator,completed a questionnaire using a five-point Likert scale comparing its performance with that of thecomputerised CAE AccuTouch.Results: Participants were largely positive about their experience (mean score of 4.76). The bronchoscopybiosimulator was found to be realistic (mean score 4.64), easy to use (mean score 4.88), and helpful inlearning to perform a variety of diagnostic and therapeutic procedures (mean score 4.85). Importantly, thebronchoscopy biosimulator compared favourably to the computer simulator (mean score 4.84).Conclusions: These data support the concept of the bronchoscopy biosimulator as an acceptable modelwith which to supplement the experience of bronchoscopic procedures.